REGULATION OF FINGERPRINTING IN CRIMINAL CASES IN INDONESIA: AUTHORITIES AND LIMITATIONS - SUISNO, SUISNO; ISNAINI, ENIK; ROYANI, AHMAD; ROCHMAWANTO, MUNIF; MULJONO, BAMBANG EKO (Universitas Islam Lamongan, 2023)
AbstractIn the stage of the criminal case investigation process will be carried out through severalprocesses, one of which is by taking fingerprints. Fingerprints, which in English are calledfingerprints or ductyloscopy, are taken in the investigation process for further examinationof evidence that may be left at the scene of the crime. This research is a normative legalresearch that reveals two main problems, first: What is the legal basis for taking fingerprintsinrevealingcriminalacts,second,howistheauthorityofinvestigatorsintakingfingerprints to reveal criminal acts. In taking fingerprints until now there has been nospecific regulation, the name in the implementation of taking fingerprints of the Police isbased on Law Number 2 of 2002 concerning the republic police and Law Number 8 of 1981concerning criminal procedure law. And the authority of investigators in taking fingerprintsis contained in Article 15 letter h of the Law on the Indonesian National Police (Law of theRepublic of Indonesia Number 2 of 2002) Jo Article 7 paragraph 1 of the CriminalProcedure Code (KUHAP).